Destruction of the flame retardant hexabromocyclododecane in a full-scale municipal solid waste incinerator. Issue 2 (February 2015) - Mark, Frank E; Vehlow, Juergen; Dresch, Hans; Dima, Bogdan; Grüttner, Werner; Horn, Joachim
Hexabromocyclododecane containing polystyrene foam obtained from the building and construction market has been co-incinerated in a full-scale waste incineration plant. The co-feeding of 1 and 2 wt% of polystyrene foam had no influence on the operation of the plant. The bromine content increased the raw gas hydrogen bromide concentration slightly. The air emission, including that of dioxins and bromine, was not altered and so was the quality of the solid residues. The hexabromocyclododecane concentrations in the solid residues were almost identical, regardless of whether or not and how much polystyrene foam was added. The obtained destruction efficiency was >99.999% independent of the amount of added polystyrene foam. This finding indicates a virtually total destruction of hexabromocyclododecane.